Pelatihan Pemasaran Instagram untuk UMKM Nasi Tumpeng Kang Ca'di: Pemanfaatan ChatGPT dan Canva - Muhammad Aththur Shadiq; Ariell Goldina Suciawan; Fedianty Rosalynda Rante Tasak; Ronny Wijaya; Aileen Chandra; William Tan; Davin Endri Setiawan; Yuyun Karystin Meilisa Suade (LPPM Stikosa - AWS, 2024)
Marketing through social media, particularly Instagram, plays a vital role in developing Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. In this context, content consistency and understanding of generative AI technology (ChatGPT) and graphic design applications (Canva) are essential factors for MSMEs. This service activity study aims to train Nasi Tumpeng Kang Ca'di MSMEs in optimizing digital marketing through ChatGPT and Canva. The training method was conducted online through Zoom, involving initial interviews, visits to MSME locations, MSME showcases, and preparation and implementation of training materials. The evaluation was conducted through questionnaires to measure the understanding and effectiveness of the training. The results showed increased MSMEs' understanding and skills in creating attractive and consistent marketing content on Instagram. This activity is expected to strengthen MSMEs' digital marketing strategies and positively impact business development in the digital era.